The contribution of psychological capital and parental age to job satisfaction: a comparison of parents of children with autism spectrum disorder and parents of typically developing children - Hazan-Liran, Batel (Frontiers in Education, 2024)
A recent concern is the frequency with which children are classified as having autistic spectrum disorder (ASD). Parents of children with ASD report difficulties in all areas of life, including the workplace. Previous studies show psychological capital (PsyCap), defined as a combination of hope, self-efficacy, optimism and resilience, is a key factor in job satisfaction and coping in numerous areas. I examined the relations of PsyCap with job satisfaction in parents of ASD children and parents of typically developing children. The study involved 141 participants, 127 women, 14 men. About half (n=69) had a child with ASD (mean age 41.41, SD 5.79), and about half (n=72) had a typically developing child (mean age 43.65, SD 7.29). Measurements comprised the Job Satisfaction Questionnaire and the PsyCap questionnaire (PCQ). Data were collected online. Positive relations between PsyCap and job satisfaction was found for both groups. Parents of children with ASD had higher levels of resilience than their comparators.With increased age, parents of children with ASD reported decreased job satisfaction; parents of typically developing children reported increased job satisfaction. The study expands the understanding of how parents of children with ASD cope at the occupational level. Their job satisfaction decreases with age. Organizations who employ parents of children with special needs in general and ASD in particular should take this into account and discuss their employees' changing needs to maximize their job satisfaction and give them room for professional development under flexible conditions.